QUALITY OF QUAIL EGGS GIVEN MORINGA LEAF FLOUR (Moringa Oleifera Lam) IN FEED - Samuel, Siti Safriayanti; Datau, Fahria; Gubali, Syukri I (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2024)
The purpose of the study was to measure the quality of quail eggs fed with Moringa leaf flour in the feed. This study used 100 quails. This study used analysis of variance (ANOVA) to analyze the quality of quail eggs. The study used a completely randomized design (CRD) with 5 (five) treatments and 4 (four) replications, and each treatment unit used 5 (five quails). The research variables were egg weight, egg shell thickness, albumen index, Haugh unit, and egg yolk color. The results showed that the administration of Moringa leaf flour had no significant effect (P0.05) on egg weight, eggshell albumen index and Haugh unit and had a significant effect (P0.05) on quail egg yolk color. Further tests showed that treatment P2 was different from P3, P0, P1 and P4, while treatment P4 was not different from treatments P3, P1 and P0. The average value of egg yolk color in treatment P3 was lower than other treatments. Duncan showed that the P2 treatment gave a better yolk color than the other treatments. It was concluded that the administration of Moringa leaf flour had the same or no different effect on egg weight, albumin index and Haugh unit. and the provision of Moringa leaf flour with a level of 4% gave a better egg yolk color. The provision of moringa leaf flour in feed did not have a significant effect (P0.05) on the egg white index and Haugh Unit (HU) of quail eggs, but had a significant effect (P0.05) on egg weight and quail egg yolk color